Carbon nanotube-nanocrystal heterostructures fabricated by electrophoretic deposition - Mahajan, S. V.; Hasan, S. A.; Cho, J.; Shaffer, M. S. P.; Boccaccini, Aldo R.; Dickerson, J. H. (Nanotechnology, 2008)
Alternating layer, carbon nanotubes-nanocrystal composite films, comprising multi-walled carbon nanotubes (MWCNTs) and iron oxide (Fe3O 4) nanocrystals, have been fabricated via electrophoretic deposition (EPD) on stainless steel and gold substrates. Low field-high current and high field-low current EPD schemes were integrated to produce the composite films. The low field-high current EPD approach produced porous mats from an aqueous suspension of the MWCNTs, while the high field-low current EPD approach produced tightly packed nanocrystal films from a dispersion of the nanocrystals in hexane. Large electric fields applied during the nanocrystal EPD and strong van der Waals interactions among the nanocrystals facilitated the formation of tightly packed nanocrystal films atop the MWCNT mats to create CNT mat-nanocrystal film composites. The surface coverage and homogeneity of the nanocrystal films improved with repeated deposition of the nanocrystals on the same mat. The assembly of nanotube mats on top of the CNT mat-nanocrystal film composite confirmed the feasibility of multilayered CNT mat-nanocrystal film heterostructures suitable for a range of devices. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) techniques were employed to characterize the surface coverage, homogeneity, and topology of these composite films. © IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.carbon_5